Effectiveness of selected mass media in agricultural technology transfer to the farmers of Bangladesh - Khan, Suzan; Rahman, M Hammadur; Uddin, Mohammed Nasir (Research in Agriculture Livestock and Fisheries, 2017)
The role of mass media in dissemination of farm information to the farmers is crucial. Thus, the study was undertaken to determine the effectiveness of selected mass media in agricultural technology transfer to farmers of Bangladesh and identify the influential factors affecting the effectiveness of mass media in technology transfer to farmers. The study was conducted in three villages of Gouripur sub-district under Mymensingh district in Bangladesh. One hundred ten farmers were interviewed using a structured questionnaire for data collection during the period of 15 May to 15 June, 2016. Both descriptive and inferential statistics were used to analyze the collected data. Results show that 62.7 per cent of the farmers perceived that effectiveness of mass media in technology transfer was low, while 31.8 per cent and 5.5 per cent of them perceived the issue as moderately effective and highly effective, respectively. Television was most popular mass media compared to radio, leaflet, poster and farm magazine based on the farmers responses. Out of eight characteristics, farmers education, extension contact and use of media had positively significant with the effectiveness of mass media. Multiple regression analysis revealed that 39.3% of the total variation in perceived effectiveness of mass media explained by two variables, namely education and use of media and identified as influential factors affecting the effectiveness of selected mass media. Res. Agric., Livest. Fish.4(1): 7-13, April 2017